Combining depot antipsychotic with an assertive monitoring programme for treating first-episode schizophrenia in a resource- constrained setting (2016)
Aim: To assess the feasibility and effectiveness of depot antipsychotic (flupentixol decanoate) combined with an assertive monitoring programme (AMP) in first-episode schizophrenia. Methods: This was a prospective, non-comparative, longitudinal study conducted over 12 months assessing patient acceptance, adherence, outcome in domains of psychopathology, functionality and quality of life, and tolerability. Results: Of 207 participants, 149 (72%) completed 12 months of treatment. Acceptance of and adherence to depot was good. Treatment response was achieved by 170 (82%) participants and remission by 124 (60%). Thirty-three (19%) responders relapsed and10(5%) participants met a priori criteria for treatment resistance. Treatment was generally well tolerated. Conclusions: Combination of depot antipsychotic with an AMP maybe an effective and safe intervention linearly phase of schizophrenia, and may be particularly suitable for resource constrained settings.